Implementasi Prinsip-Prinsip Manajemen Pembelajaran PAI di Sekolah Dasar - Kholil, Muhamad; Hanin, Jihan Al; Fairuz, Sayida Abqaria; Zaman, Badrus (Al-Abshar: Journal of Islamic Education Management, 2024)
The principles of learning Islamic religious education in elementary schools are something that every Islamic religious education teacher must use in teaching. The aim of this research is to provide an understanding regarding the implementation of principles that can be used by a teacher when teaching so that the implementation is in accordance with the objectives of learning Islamic religious education itself. In this research, we used a literature study method by collecting various kinds of reading that were in accordance with the major themes taken. The results of this research are that there are various kinds of learning principles that can be used in a learning process, however, in Islamic religious education learning, several principles can be used, namely full attention of students, development of students' potential, and a variety of learning methods that can be implemented in various ways. One of the learning models is quantum teaching for elementary schools